Why does solvent treatment increase the conductivity of PEDOT : PSS? Insight from molecular dynamics simulations. Issue 36 (8th September 2022) - Modarresi, Mohsen; Zozoulenko, Igor
Abstract : The mechanism of PEDOT : PSS conductivity enhancement after polar solvent treatment. Abstract : Poly(3, 4-ethylenedioxythiophene) : polystyrene sulfonate (PEDOT : PSS) is one of the most important conducting polymers. In its pristine form its electrical conductivity is low, but it can be enhanced by several orders of magnitude by solvent treatment, e.g. dimethyl sulfoxide (DMSO). There are various (and often conflicting) explanations of this effect suggested in the experimental literature, but its theoretical understanding based on simulation and modelling accounting for the complex realistic morphology of PEDOT : PSS is missing. Here, we report Martini coarse-grained molecular dynamics simulation for the DMSO solvent treatment of the PEDOT : PSS film. We show that during solvent treatment a part of the deprotonated PSS chains are dissolved in the electrolyte. After the solvent treatment and subsequent drying, the PEDOT-rich regions become closer to each other, with a part of the PEDOT chains penetrating into the PSS-rich regions. This leads to an efficient coupling between PEDOT-rich regions, leading to the enhancement of the conductivity. Another factor leading to the conductivity improvement is the π–π stacking enhancement resulting in more π–π stacks in the film and in the increased average size of PEDOT crystallites. Our results demonstrate that course-grained molecular dynamics simulations of a realistic system represent a powerful tool enabling theoretical understanding of important morphological features of conducting polymers, which, in turn, represents a prerequisite for materials design and improvement.